User Experience: A Bibliometric Review of the Literature - Wuheng Zuo; Baijun Mu; Hui Fang; Yuehua Wan (IEEE Access, 2023)
User experience is a well-discussed topic in the field of human–computer interaction. To describe the status of research on this topic, a bibliometric analysis of publications concerning user experience from 2011 to 2021 was conducted using the Web of Science database. The main functions of Derwent Data Analyzer software include data cleaning, mining, and visualization. The historical trends of the year, leading countries, leading institutions, major contributors, and leading research fields and journals were investigated, and a keyword analysis of the highly cited literature was performed. The key findings are as follows. The United States, China, and Britain are the three most productive countries. Tsinghua University in China is the most productive organization, and Sungkyunkwan University in South Korea has the highest average citations per publication. User experience has attracted the attention of numerous scholars in 204 research fields, and computer science information systems is the main field. “Usability,” “virtual reality,” “human–computer interaction,” and “augmented reality” are the most used keywords. A recent trend is the focus on molecular biology.